Do banks time bond issuance to trigger disclosure, due diligence, and investor scrutiny? - Covitz, Daniel M.; Harrison, Paul (Journal of Financial Intermediation, 2004)
This paper tests a new hypothesis that bank managers issue public debt, at least in part, to convey positive, private information and refrain from issuance to hide negative, private information. This “positive selection” hypothesis is tested against the traditional “adverse selection” hypothesis. We find evidence for “positive selection,” using ratings migrations, equity returns, bond issuance, and balance sheet data for US bank holding companies. The results add to our understanding of “market discipline” in monitoring bank holding companies and also inform upon how proposed regulatory requirements that banking organizations frequently issue public debt might augment “market discipline.”